If it's not what You are looking for type in the equation solver your own equation and let us solve it.
33=-6m+9
We move all terms to the left:
33-(-6m+9)=0
We get rid of parentheses
6m-9+33=0
We add all the numbers together, and all the variables
6m+24=0
We move all terms containing m to the left, all other terms to the right
6m=-24
m=-24/6
m=-4
| 2(x+6)=x–7 | | 6m-7/8=2/3 | | 5=56-8x | | p-35=3 | | 45-4y=y | | 5=-6x-1 | | 30-2(x+4)=50 | | 1/2x-9=13+6x | | 100+40x=100+42x | | 4a+8=4(a+2 | | Y=x^2+7x-11 | | -2x-1(8x+1)=10 | | 9(k+8)=47+4k | | 8=12x–16 | | -3x+7+8x+5-x=8 | | 3u+22=2u-7u | | -5(-x-6)=-20 | | -2.25+5/8=v | | 3c(2c+2)=9 | | 4a+8=a*(a+2) | | 19-11=4(x-8) | | -5(-x-6=-20 | | 7x+6=24+4x | | (x+8)-10=8(x-8) | | –6+3m=10+m | | 5r-24=16 | | -u+u=-5 | | 3/4-(-3/12)=x | | 8=-6+u/2 | | p+18=3p-12 | | -21/4+5/8=v | | 12^3-20x^2+x+3=0 |